Measurement of pneumococcal IgG antibody, carriage and infection with Streptococcus pneumoniae in children under five years of age with acute respiratory infection in Niger - Dan D. Ibrahim; Sani Ousmane; Kamayé Moumouni; Ali E. Mahamane (Elsevier, 2017)
Pneumonia is the major cause of mortality in children under five years.A total of 751 children aged 1-59 months admitted for acute respiratory infection were included in this study. Pneumococcal serum IgG antibody was determined by ELISA. Carriage of Streptococcus pneumoniae was determined by molecular analyses of nasopharyngeal swabbings, and the rapid urinary diagnostic test Binax NOW® Sp was used for detection of pneumococcal antigen in urine.A total of 224 (29.8%) children had vaccination record books, and among them, 186 (83%) were vaccinated with the 23-Valent Pneumococcal Polysaccharide Vaccine (PPSV-23), 7 (3%) were vaccinated with the 13-Valent Pneumococcal Conjugate Vaccine (PCV-13), and 31 (14%) had not been vaccinated. IgG levels against pneumococcal polysaccharide were ≥1.3 μg/mL in most of the children (99.4%). The carriage rate of S. pneumoniae was 39%, and the Binax NOW® Sp test was positive in 26% of children. There was no significant variation between the means of IgG concentrations against pneumococcal polysaccharides as related to vaccination status, age and nasopharyngeal carriage of S. pneumoniae. However, there was a weak positive correlation between age and level of IgG (r = 0.08; p = 0.021), and there was a significant variation (p = 0.038) of the IgG level according to presence of S. pneumoniae antigen in urine. The presence of S. pneumoniae antigen in urine is significantly (p ≤ 0.01) higher in children with nasopharyngeal carriage of S. pneumoniae (40%) than non-carriers (20%).This study shows that S. pneumoniae has high circulation in children under the age of five years either through infection or carriage. Keywords: Pneumococcal antibody, Carriage, Respiratory infection, Children under five years